Is social licence a response to government and market failures? Evidence from the literature. (December 2020) - Dumbrell, Nikki P.; Adamson, David; Wheeler, Sarah Ann
Abstract: The term 'social licence to operate', introduced in the 1990s, has increasingly been used to describe the social and environmental standards for firms to meet. Formally, a firm with a social licence is said to enjoy (intangible) ongoing acceptance or approval by communities and other stakeholders that: (1) are affected by the firm and/or their activities; and (2) can influence the profitability of the firm. While the mining industry was the first to identify the need to obtain a social licence to operate, other sectors also recognise its importance. Growth in the frequency and breadth of the terms use has contributed to a substantial body of research. A focus of this research has been the benefits and costs experienced by affected stakeholders as a result of a firm's activities. This suggests that social licence is, partly at least, an economic issue. We conducted a systematic review (with a final database of 651 documents) of the social licence literature to identify what conceptual themes have emerged, and discuss how these conceptual themes relate to fundamentals of welfare economics. By introducing economic perspectives, it was found that social licence concerns stem from government and market failures, namely: (1) negative externalities; (2) undersupply of/threats to public goods; and (3) use of socially valuable assets to generate private profits. We argue that classifying social licence concerns in this way brings clarity to the social licence literature. Highlights: A systematic review of social licence literature highlights key research themes. Research is focussed on natural resource industries and resource-rich countries. Social licence concerns stem from government and market failures. Negative externalities are a key driver of social licence concern. Stakeholders withhold social licence/s to demand improved social welfare outcomes.